Analysis of the Paradigm Shift in the Right to Education during a Pandemic for Students from a Human Rights Perspective - M. Afif Hasbullah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to analyze access to the paradigm shift in the right to education during the pandemic for students from the perspective of human rights. This study uses a type of juridical-normative research. The primary legal sources used in this research are the 1945 Constitution of the Republic of Indonesia, Law No. 20 of 2003 concerning the National Education System, the 1948 Universal Declaration of Human Rights, and the International Covenant on Economic, Social and Cultural Rights. The types of legal sources used in this study are primary and secondary sources of law. Based on the analysis of legal sources, it can be concluded that the implementation of education is a right to education protected by the 1945 Constitution of the Republic of Indonesia and confirmed by the Human Rights Act. Understanding the right to education is more broadly understood as obtaining educational services in various forms/methods of online learning. Learning to use internet media also confirms that the right to education is closely related to the completion of the right to information following Articles 13, 14 and 15 of the Covenant on Economic, Social and Cultural Rights.